LEGAL PROBLEMS OF STRUGGLE WITH COMPUTER CRIMES - V. M. Bykov; V. N. Tcherkasov (Russian Journal of Economics and Law)
The concepts that are scantily studied in science of a criminal law as the computer information, a proportion of data and information, and also their bearers are considered in the article. The authors analyze the nature of the information disposal, mark such feature of the computer information as the absence of such concepts as the original and the copy; mark the complexity in a cost determination of the information. The authors note, that ethical standards in information sphere, and also complexity in the decision of questions and estimations of actions of subjects of crimes in the sphere of their illegalities are also insufficiently developed and considered.